INOVASI DALAM PENGELOLAAN LIMBAH FARMASI: STRATEGI EFISIEN UNTUK MENGURANGI DAMPAK LINGKUNGAN DAN MENJAGA KESEHATAN MASYARAKAT - Irma Nadia Yanti; Marisa Susanti; Nor Latifah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Pharmaceutical waste has become an increasingly urgent issue, particularly with the rising amounts of expired medicines and unused pharmaceuticals. Improper management of pharmaceutical waste can lead to contamination of water, soil, and air, posing risks to ecosystems and human health. This article discusses innovations and efficient strategies for managing pharmaceutical waste, including the use of environmentally friendly processing technologies, the implementation of circular economy principles, and the repurposing of pharmaceutical waste into other products. Additionally, it highlights the importance of collaboration between the government, industry, and society in managing pharmaceutical waste more effectively and efficiently. It is hoped that the implementation of these solutions will make pharmaceutical waste management more sustainable, benefiting both human health and environmental preservation.